ROLE OF MICRO CREDIT IN POVERTY ERADICATION: A CASE STUDY IN CHITTOOR RURAL MANDAL OF ANDHRA PRADESH - Muralimohan, M.; Devarajulu, M. (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
Recently the concept of micro credit has been given huge prominence at the global level in order to eliminate poverty and to raise the living conditions of underprivileged and growth excluded groups across the world countries. Community development and poverty eradication through micro credit which combines use of training, organization and career development, efforts to improve individual, group and organizational effectiveness develops the essential abilities that enable individuals to perform present and future income generation through planned learning activities. This is not only related to those who are employed but also it is necessary even for those who are socially and economically backward sections and groups to improve their living standards and empowerment. The essential credit supplied at an affordable rate and in time for those who have the capacity to invest it in a suitable productive manner could help to improve their social and economic standards. Many of studies throughout the world evidently concluded that the reliable and affordable credit helps the poor to come out from the vicious circles of poverty. This paper has made an attempt to describe the role of micro credit in eradication of poverty by estimating income generating opportunities and income levels raised by micro credit supplied through self-help groups which results in lifting the rural poor from the poverty crunch in Chittoor rural mandal of Andhra Pradesh.